Pengembangan LKPD Teori Probabilitas Berbasis Model Pembelajaran Contextual Teaching And Learning (CTL) di Prodi Pendidikan Matematika Universitas Batanghari - Relawati, Relawati; Syarifuddin, Amir; Supriyati, Supriyati; Riwayati, Selvi (Jurnal Ilmiah Dikdaya, 2024)
This research is motivated by facts at the research location. Based on the results of initialobservations at the Mathematics Education Study Program, FKIP UNBARI, it was found that if we observedfurther, during the lecture process we found symptoms that were less supportive of conducive learning. Thesesymptoms include students not maximizing their high-level thinking abilities, and being less motivated to studymore diligently. Referring to the research objectives that have been stated, the type of research used is researchand development. The development model used is the ADDIE (Analyze, Design, Development, Implementation,Evaluation) development model. The research results show that the Probability Theory LKPD based on the CTLlearning model developed for Probability Theory lectures is very valid, both in terms of content and construct,practical and effective and the workbook is in accordance with learning outcomes and syllabus